PENGARUH BUDAYA ORGANISASI, KEPUASAN KERJA DAN KEPEMIMPINAN MANAJER TERHADAP KINERJA KARYAWAN DI HOTEL BEST WESTERN PREMIER THE HIVE CAWANG - Efiani Efiani; Verry Cyasmoro; Vina Espirapika (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this research is to test influences of Organization Culture, Leadership Style toward Job Satisfaction. The samples of this research consisted of one hundred employees’s Hotel Best Western Premier the Hive Cawang. Analysis technique use SPSS software. The result of the analysis showed that Organization Culture and Leadership Style contributes an positive influence which is significant to Job Satisfaction, Job Satisfaction contributes an positive influence which is significant to Organizational Commitment, Organization Culture contributes an positive influence which is significant to Employee’s Performance, Leadership Style contributes an positive influence which is significant to Employee’s Performance, Organization Culture, Leadership Style and Job Satisfaction contributes an positive influence which is significant to Employee’s Performance using Organizational Commitment . This empirical result indicated that in order to raise the standarts of a Organization Culture, Leadership Style and Job Satisfaction, because the lower of Employee’s Performance, management should focus on factor such as Culture, Leadership Style, Job Satisfaction and Organizational Commitment because leverage Organization Commitment, Job Satisfaction and Employee’s Performance depend on it. Theoritical implications and suggestions for future research have been elaborated at the end of this study.